Hydrosolidarity di Sungai Nil: Peran Nile Basin Initiative dalam Manajemen Sungai Lintas Batas - Muhammad Aditya Purnomo (Parahyangan Center for International Studies, 2022)
This article aims to explain the importance of NBI’s role in Nile River management. Transboundary basins are important water resources for 2 billion lives across the world. Those basins fulfil domestic water, drinking water, agriculture, industry, and electric generator needs. In north-east of Africa, Nile river plays the important role for its eleven riparian states. Nile river, being the longest river in the world, supports the lives of more than 300 million people, and the number is estimated to rise greatly in three to four decades in the future. The increase of population will affect the availability of water as the demands of agriculture, domestic, and industry grow. Nile riparian states realized that the best option in using, protecting, and managing the river in a sustainable and integrated manner is through international cooperation. In 1999, Nile Basin Initiative (NBI) was established with Nile riparian states as its member, with the purpose of facilitating discussions of cooperation regarding the management of the river. This article uses the theory of hydrosolidarity. Results show that NBI has important roles in Nile river management, namely in the creation of a cooperative institutional structure, supporting stakeholder participations, supporting data and knowledge sharing, and supporting integrations and linkages. Keywords: Hydrosolidarity; Nile Basin Initiative; Nile River; Transboundary River